Dry period length affects rumen adaptation in dairy cattle precalving and during the first weeks after calving - R.M.A. Goselink; A.T.M. van Knegsel; A. Bannink; R.M. Bruckmaier; J. Dijkstra; G. van Duinkerken; J.T. Schonewille; W.H. Hendriks (Journal of Dairy Science, 2024)
ABSTRACT: Omitting or shortening the dry period may result in a fairly constant ration throughout the transition period of dairy cows, reducing the need for adaptation of cow metabolism and rumen function to a new lactation. The objective of this study was to determine the effect of dry period length (DP) on rumen adaptation and cow metabolic state during the transition period. Twelve pregnant, rumen-cannulated Holstein Friesian dairy cows at the end of their first lactation were assigned to 1 of 3 treatments: a conventional (60 d), short (30 d), or no dry period (0 d). At dry-off, cows received a dry-cow ration until calving. Lactating cows received a lactation ration. Cows were monitored from 8 wk before calving until 8 wk after calving for milk yield and DMI. Rumen biopsies were taken from 3 locations in the rumen at 60, 40, and 10 d before calving and 3, 7, 14, 28, and 56 d after calving to assess papillae dimensions. Blood was sampled weekly from 3 wk before until 8 wk after calving, and liver biopsies were taken at wk −2, 2, and 4 relative to calving. Prepartum, DMI, and milk yield were greater for cows with a short or no dry period, compared with cows with a conventional dry period. Postpartum, DMI was greater for cows with a short dry period compared with cows with a conventional dry period. Plasma glucose concentration was greater for cows without a dry period, compared with the other DP postpartum. Plasma concentrations of nonesterified fatty acids and BHB, and liver triglyceride content, did not differ among dry period. Rumen papillae differed in size based on biopsy location, but there was no interaction between biopsy location and the effect of DP. Rumen papillae surface area for cows managed for a 30- or 60-d dry period decreased toward calving. At 40 d prepartum, papillae surface area was greater for short and no dry period treatment compared with a conventional dry period. At 10 d prepartum, papillae surface area was greater for the no dry period treatment compared with both other treatments, and this difference was still present 3 d postpartum. Cows managed for a short dry period showed faster increase in papillae dimensions after calving compared with cows managed for a conventional dry period. From d 28 onwards, no differences in papillae surface area were observed. The faster rumen adaptation postpartum may be related to the increased DMI during the first weeks postpartum for cows managed for a short dry period. However, this did not result in improved metabolic status or milk yield. The results from the present study demonstrate that the dietary changes related to a conventional DP affected rumen papillae development, not only prepartum but also early postpartum. Further optimization of DP as well as dietary composition throughout the transition period may support cows in their adaptation to a new lactation.